From dark matter halos to pre-stellar cores: high resolution follow-up of cosmological Lyman-Werner simulations - Prole, Lewis R.; Schauer, Anna T P; Clark, Paul C; Glover, Simon; Priestley, Felix D; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2023)
Molecular hydrogen allows cooling in primordial gas, facilitating its collapse into Population III stars within primordial halos. Lyman-Werner (LW) radiation from these stars can escape the halo and delay further star formation by destroying H2 in other halos. As cosmological simulations show that increasing the background LW field strength increases the average halo mass required for star formation, we perform follow-up simulations of selected halos to investigate the knock-on effects this has on the Population III IMF. We follow 5 halos for each of the J21 = 0, 0.01, and 0.1 LW field strengths, resolving the pre-stellar core density of 10−6 g cm−3 (1018 cm−3) before inserting sink particles and following the fragmentation behaviour for hundreds of years further. We find that the mass accreted onto sinks by the end of the simulations is proportional to the mass within the ∼10−2 pc molecular core, which is not correlated to the initial mass of the halo. As such, the IMFs for masses above the brown dwarf limit show little dependence on the LW strength, although they do show variance in the number of low-mass clumps formed. As the range of background LW field strengths tested here covers the most likely values from literature, we conclude that the IMF for so-called Pop III.2 stars is not significantly different from the initial population of Pop III.1 stars. The primordial IMF therefore likely remains unchanged until the formation of the next generation of Population II stars.